Evaluation and Selection of Potential Biomass Sources of North-East India towards Sustainable Bioethanol Production - Nongthombam, Grihalakshmi D.; Labala, Rajendra K.; Das, Sudripta; Handique, Pratap J.; Talukdar, Narayan C. (Frontiers in Energy Research, 2017)
Vegetation biomass production in North-East India within Indo-Burma biodiversity hotspot is luxuriant and available from April to October to consider their potential for bioethanol production. Potential of six lignocellulosic biomass (LCB) sources; namely, sugarcane bagasse (BG), cassava aerial parts (CS), ficus fruits (Ficus cunia) (FF), “phumdi” (floating biomass), rice straw (RS), and sawdust were investigated for bioethanol production using standard techniques. Morphological and chemical changes were evaluated by Scanning electron microscopy and Fourier transform infrared spectroscopy and quantity of sugars and inhibitors in LCB were determined by High performance liquid chromatography. Hydrothermally treated BG, CS, and FF released 954.54, 1,354.33, and 1,347.94 mg/L glucose and 779.31, 612.27, and 1,570.11 mg/L of xylose, respectively. Inhibitors produced due to effect of hydrothermal pretreatment ranged from 42.8 to 145.78 mg/L acetic acid, below detection level (BDL) to 17.7 µg/L 5-hydroxymethylfurfural, and BDL to 56.78 µg/L furfural. The saccharification efficiency of hydrothermally treated LCB (1.35–28.64%) was significantly higher compared with their native counterparts (0.81–17.97%). Consolidated bioprocessing of the LCB using MTCC 1755 (Fusarium oxysporum) resulted in maximum ethanol concentration of 0.85 g/L and corresponded to 42 mg ethanol per gram of hydrothermally treated BG in 120 h followed by 0.83 g/L corresponding to 41.5 mg/g of untreated CS in 144 h. These ethanol concentrations corresponded to 23.43 and 21.54% of theoretical ethanol yield, respectively. LCB of CS and FF emerged as a suitable material to be subjected to test for enhanced ethanol production in future experiments through efficient fermentative microbial strains, appropriate enzyme loadings, and standardization of other fermentation parameters.